Predictors of Neonatal Mortality in Ethiopia: A Comprehensive Review of Follow-Up Studies - Derara Girma; Hiwot Dejene; Leta Adugna (International Journal of Pediatrics)
Background. Neonatal mortality remains a prominent public health problem in developing countries. Particularly, Ethiopia has a higher neonatal mortality rate than the average sub-Saharan African countries. Hereafter, this review article was aimed at synthesizing existing predictors of neonatal mortality in Ethiopia. Methods. A systematic search and review of peer-reviewed articles were conducted on the predictors of neonatal mortality in Ethiopia. A search of key terms across different databases including Web of Science, SCOPUS, Cochrane Library, PubMed, EMBASE, Hinari, and Google Scholar was conducted, supplemented by reference screening. The SANRA tool was used to critically appraise studies included in the review. Results. After removing duplicates and applying the eligibility criteria, 14 of the 64 initially identified articles were included in the final review. These were original articles published between 2011 and 2021. The identified predictors were narrated and presented under different domains. Accordingly, sociodemographic predictors such as residence, distance from the health facility, and maternal age; service delivery-related predictors such as no ANC follow-up, not taking iron-folic acid supplementation during pregnancy, and no PNC visit; neonate-related predictors such as low birth weight, extreme prematurity/preterm, and low APGAR score; pregnancy and childbirth-related predictors such as birth interval<18 months, twin pregnancy, and time of rupture of membrane>12 hours; and maternal-related predictors such as maternal HIV infection, maternal childbirth-related complications, and maternal near-miss were stated to increase a likelihood of newborn death in Ethiopia. Conclusion. Public health interventions directed at decreasing neonatal mortality should address the rural residents, mothers not having ANC follow-up, low birth weight, twin pregnancy, and maternal HIV infection. The wealth of data gathered during primary research should not only lead to identification of predictors, but should also provide guidance for health system intervention strategies in a country aiming to reduce neonatal mortality.